Policy of Inclusive Education for Education for All in Indonesia - Asal Wahyuni Erlin Mulyadi (Indonesian Association for Public Administration, 2017)
The purpose of this article is to discuss the basic and essential contents of the policy of inclusive education in Indonesia. Inclusive education is the recent worldwide agenda for educational reform toward the no-discrimination in education. Regardless of any condition and circumstances, it is guaranteed that every child has the right for education, as it is also clearly highlighted in the global program of Education for All (EFA). This paper is a content and analytic review on the national policy of inclusive education towards the education for all in Indonesia, i.e the Regulation of National Ministry of Education (PERMENDIKNAS) Number 70 Year 2009. Number of schools implementing the inclusive education policy has significantly increased, supported also by the province and district related regulations. However, the context of the policy of inclusive education as the major guideline for the policy implementation lead to various and even narrowed perspective on the concept of inclusion. Inclusive education is still discussed more in term of learners with disabilities only. Much progress has been made, yet it is still much left to be accomplished to achieve the fundamental and universal rights on education to all society.